Makna Upacara Pawintenan Bagi Umat Hindu Di Desa Batu Nindan Kecamatan Basarang Kabupaten Kapuas - Ni Wayan Gateri (Jayapangus Press, 2022)
Pemangku as someone who leads the ceremonial process in Hinduism must be someone who has Viveka Jnana and has gone through the process of the marriage ceremony. Pemangku marriage ceremony can be divided into three types, namely Sari Pawintenan, 2) Mepedamel Pawintenan, 3) Samskara Eka Jati Pawintenan. This study aims to determine the meaning of the wedding ceremony carried out by prospective Pemangku in Batu Nindan Village, Kapuas Regency. Descriptive qualitative research methods are used in this study to solve problems. The marriage ceremony is a stage that must be passed by someone to become a Pemangku. The implementation of the marriage ceremony from generation to generation aims to legitimize someone as a Pemangku on a scale and niskala basis. The marriage ceremony also has the aim of purifying the prospective stakeholder physically and mentally so that in carrying out his duties as a Pemangku it can be carried out sincerely in accordance with the guidance of Ida Sang Hyang Widhi Wasa. A person who has gone through a stakeholder marriage ceremony is given the freedom of ayah-ayahan banjar because a Pemangku provides services to the people regardless of time. Based on research conducted in Batu Nindan Village, it was concluded that the marriage ceremony has a religious meaning, a social meaning for service to the people, and a cultural meaning.